2023
DOI: 10.1101/2023.09.25.559407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbially-catalyzed conjugation of GABA and tyramine to bile acids

Michael W. Mullowney,
Aretha Fiebig,
Matthew K. Schnizlein
et al.

Abstract: Bile acids (BAs) are cholesterol-derived molecules in the human gut that aid in digestion and nutrient absorption, regulate host metabolic processes, and influence gut microbiome composition. Both the host and its microbiome contribute to enzymatic modifications that shape the chemical diversity of BAs in the gut. Several bacterial species have been reported to conjugate standard amino acids to BAs, but it was not known if bacteria conjugate other classes of amines to BAs. We show thatBacteroides fragilisstrai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Inspecting plausible annotations of the delta masses by matching to multiple databases (see STAR Methods), revealed several candidates from the polyamine biosynthetic pathway (Figure 4A; Table S4). Consistent with our observations that polyamines and their biosynthetic precursors are conjugated to bile acids, while this paper was in review, the polyamine, g-aminobutyric acid (GABA), was shown in two preprints to be conjugated to deoxycholic acid by microbes belonging to species Bacteroides fragilis, Mediterraneibacter gnavus, Bifidobacterium longum, and Bacteroides ovatus isolated from the J-pouch of a patient suffering from ulcerative colitis pouchitis 74 and lithocholic GABA amidates and as ester when chenodeoxycholic acid or lithocholic acid were added to human stool, ex vivo. 75 Given that polyamines are involved in several cellular processes, including transcription, translation, stress protection, metabolism, growth, and aging, and that they are involved in many diseases, such as cancer and neurodegeneration, 76,77 we were interested in pursuing our investigation of these putative polyamine bile amidates.…”
Section: Llsupporting
confidence: 80%
“…Inspecting plausible annotations of the delta masses by matching to multiple databases (see STAR Methods), revealed several candidates from the polyamine biosynthetic pathway (Figure 4A; Table S4). Consistent with our observations that polyamines and their biosynthetic precursors are conjugated to bile acids, while this paper was in review, the polyamine, g-aminobutyric acid (GABA), was shown in two preprints to be conjugated to deoxycholic acid by microbes belonging to species Bacteroides fragilis, Mediterraneibacter gnavus, Bifidobacterium longum, and Bacteroides ovatus isolated from the J-pouch of a patient suffering from ulcerative colitis pouchitis 74 and lithocholic GABA amidates and as ester when chenodeoxycholic acid or lithocholic acid were added to human stool, ex vivo. 75 Given that polyamines are involved in several cellular processes, including transcription, translation, stress protection, metabolism, growth, and aging, and that they are involved in many diseases, such as cancer and neurodegeneration, 76,77 we were interested in pursuing our investigation of these putative polyamine bile amidates.…”
Section: Llsupporting
confidence: 80%
“…DC concentrations that attenuated growth of B. fragilis P207 in vitro are similar to those found in healthy individuals. DC was undetectable in the stool of patient 207 ( 74 ) when B. fragilis P207 bloomed to become the dominant species in the pouch ( 24 ). Thus, it is reasonable to conclude that the absence of deoxycholate contributed, at least in part, to the population expansion of B. fragilis in patient 207, though other factors relating to the overall metabolic versatility of B. fragilis ( 75 , 76 ) likely contributed to its bloom as well.…”
Section: Discussionmentioning
confidence: 99%